Detection Student Misconception in Chemical Bonding using a Virtual Reality-Integrated Two-Tier Multiple-Choice Instrument with Ethnochemistry Context - Pamungkas, Yoga Prasetyo; Yamtinah, Sri; Saputro, Sulistyo; Shidiq, Ari Syahidul (FKIP Universitas Lampung, 2024)
Two-Tier Multiple Choice Virtual Reality (TTMCVR) with ethnochemical content is used to measure the level of misconceptions and understanding of students on chemical bond materials that have good quality and tested. This development aims to test the readability and effectiveness of TTMCVR based on the results of validity and limited trials as a reference that the developed assessment is feasible to use to identify students' misconceptions and understanding of chemical bonding materials. This research method applies Research and Development (R&D) with the ADDIE model (Analysis, design, development, implementation and evaluation). This study used 18 students and 3 teachers in 3 public high schools in Surakarta. The sampling technique used purposive sampling. Data obtained in the form of instrument results include interview tests, TTMCVR assessments and open-ended questionnaires. The results showed that TTMCVR obtained validation based on aspects of context, language, and construction on the items and storyboard from 16 experts, namely 9 chemistry education lecturers from UNS, UNY and UM and 7 high school chemistry teachers in Surakarta resulting in 15 items and 16 valid storyboard indicators with Aiken index ≥ 0.73. The limited trial stage shows that TTMCVR is able to detect the level of understanding and misconceptions of students with criteria, namely understanding the concept of 26%, misconceptions 32% and not understanding 41% on ethnochemically charged chemical bonding material on ice gempol pleret. In addition, TTMCVR is classified as having a high level of readability and effectiveness as an assessment assessment from the material and media aspects of 90% from student responses and teacher responses. Therefore, it can be concluded that based on the validity and readability of TTMCVR, it is feasible to be further developed for assessment. Keywords: chemical bonding, ethnochemistry, misconceptions, two-tier multiple choice virtual reality.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1498-1517